ROLES OF FACULTY IN TEACHING ASYNCHRONOUS UNDERGRADUATE COURSES - Morris, Libby V.; Xu, Haixia; Finnegan, Catherine L. (Online Learning, 2005)
Although the availability of web-based education and the number of totally asynchronous courses have grown exponentially in the last decade, the literature on online instruction offers limited empirical guidance to faculty teaching in this environment. Much of the literature is anecdotal and prescriptive, and much more research needs to be done to situate research in practice settings. This study examines faculty roles in the online environment through the perceptions of faculty teaching online and through the archival analysis of their courses. Data were collected through document analysis of ten online courses and from interviews with thirteen instructors in the humanities and social sciences. Using Berge’s typology of online facilitator roles, this study examined the relationship between roles as perceived and enacted by faculty, identified wide variations in faculty roles and participation between experienced and novice instructors, and explored the relationship between faculty workload and perception of facilitation in the online environment. Directions for future research are suggested.